Le secteur phoenicicole algérien : Situation et perspectives à l'horizon 2010 - Messar E.M. (Le palmier dattier dans l'agriculture d'oasis des pays méditerranéens, 1993)
Date palm farming remains the pivot of the Saharan agriculture strategy. Its problems are analysed under different aspects: potentials, technical constraints and socioeconomic concerns. The development perspectives projected for 2010 aim at the rehabilitation, the enlargement and promotion of date palm production and the reconquest of the international market.
Journées Internationales d'Elche sur le Palmier Dattier dans L'Agriculture d'Oasis des Pays Méditerranéens, 25-27 Apr 1995, Elche (Spain)